Multiplex Real-Time PCR For The Detection Of Pathogenic Intestinal Parasites And Comparison With Parasitological Techniques - Basuni, Madihah (2012)
Intestinal parasitic infections by helminths and protozoa are among the most prevalent infections and remain a major public health burden in underdeveloped countries. Most intestinal helminth infections cause abdominal pain accompanied by aneroxia, nausea and diarrhea while intestinal protozoa cause diarrheal diseases. Routine diagnostic methods for intestinal parasitic infections which rely heavily on microscopic detection are insensitive, and require well-trained microscopists to avoid misdiagnosis or overdiagnosis of the infection. These limitations have led to the development of highly sensitive DNA-based assays. PCR has been proven to be sensitive and specific for detection of enteric pathogens. Since conventional PCR is time consuming and prone to cross-contamination, it is desirable to develop a realtime PCR assay which is rapid and can provide quantitative and real-time information on the amplified products. In this study, a real-time multiplex PCR assay for the detection of closely related intestinal helminths namely Ascaris lumbricoides, Strongyloides stercoralis, Necator americanus and Ancylostoma duodenale and an assay for the detection of three closely related intestinal protozoa which comprised Entamoeba histolytica, Cryptosporidium parvum and Giardia lamblia were optimized and evaluated.